Soot oxidation over Pt-loaded CeO2-ZrO2 catalysts under gasoline exhaust conditions: Soot-catalyst contact efficiency and Pt chemical state. (15th February 2023) - Yao, Peng; Huang, Yun; Jiao, Yi; Xu, Haidi; Wang, Jianli; Chen, Yaoqiang
Graphical abstract: Highlights: Soot oxidation activity was greatly improved by regulating contact efficiency and Pt chemical state. Porous CeO2 -ZrO2 was obtained by microsphere template assisted method. Liquid phase reduction method is an effective and controllable way to obtain metallic Pt species. Metallic Pt species is conducive to soot oxidation in O2 /N2 . Soot oxidation mechanism under different soot-contact efficiency and noble metal states in different atmospheres was proposed. Abstract: Decreasing the ignition temperature of soot combustion is a key of the improved catalyst performances, but a much lower concentration of oxygen from gasoline vehicle exhaust makes the research of the catalyst extremely challenging. Improving the adsorption and activation of oxygen molecules on the catalyst surface and the effective migration rate of active oxygen species are the key factors to enhance soot oxidation. In this work, Pt/CeO2 -ZrO2 -re catalyst was synthesized by synergistically adjusting CeO2 -ZrO2 pore structure and Pt chemical state, as a result, the conversion temperature (T50, 50% soot was oxidized) was reduced by 113 ℃ in 1% O2 /N2 . The pore structure of CeO2 -ZrO2 was optimized by copolymerization microsphere template assisted method, and better soot-contact efficiency and intrinsic properties were obtained, resulting in a higher availability of reactive oxygen species. In addition, adjusting Pt chemical state by using the liquid phase reduction method is significant for the adsorption and activation of oxygen molecules and catalytic cycle of soot oxidation. Structure-activity relationship studies showed that soot oxidation performance is highly related to the initial oxidation state of Pt and pore structure in 1% O2 /N2 . Better soot-contact efficiency, improved intrinsic properties and the existence of metallic Pt are responsible for the higher soot oxidation activity of Pt/CeO2 -ZrO2 -re catalyst.